English numerical set expressions with reference to Vietnamese / Nguyễn Thu Hường; NHDKH Assoc.Prof.Dr Ho Ngoc Trung - Nguyễn, Thu Hường
The purpose of this study is to investigate the linguistic features and cultural characteristics of English set expressions containing numbers. Through their syntactic features, semantic features and cultural characteristics we find out the similarities and differences between English set expressions and Vietnamese ones under the light of contrastive analysis and cross-cultural perspective. Data used for analysis in this study were mainly collected through dictionaries and the internet. Through analysis of forms of set expressions containing numbers in English and Vietnamese, it is deduced that idioms are really important in communication. Idioms are used to express ideas in figurative styles. They bring vividness and richness to the speakers’ speeches. The findings of the thesis illustrate some implications for teachers and learners of English from the use of linguistic features of set expressions containing numbers in English and focus on the meanings of English set expressions containing numbers in English and a comparative analysis with Vietnamese ones. Hopefully, the study may help learners, teachers, and translators of English avoid difficulties in realizing and translating English numerical set expressions into Vietnamese.